2009
DOI: 10.1177/230949900901700209
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Total Knee Arthroplasty Using Computer-Assisted Navigation versus Conventional Guiding Systems: A Prospective Study

et al.

Abstract: Computer-assisted navigation gives a more consistent alignment correction and reduces outliers during implant positioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 27 publications
2
34
0
2
Order By: Relevance
“…The most commonly used method of setting coronal component alignment in TKA is an extramedullary tibial and an intramedullary femoral alignment guide, but this method has shown a limited degree of accuracy [2,3,5,21,30]. Although computer-assisted surgical techniques have consistently demonstrated improved alignment accuracy versus standard guides [3,13,16,19,27,32], the increased capital costs, operative times, learning curve, and unproven functional benefits associated with their use have limited their widespread acceptance [9].…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used method of setting coronal component alignment in TKA is an extramedullary tibial and an intramedullary femoral alignment guide, but this method has shown a limited degree of accuracy [2,3,5,21,30]. Although computer-assisted surgical techniques have consistently demonstrated improved alignment accuracy versus standard guides [3,13,16,19,27,32], the increased capital costs, operative times, learning curve, and unproven functional benefits associated with their use have limited their widespread acceptance [9].…”
Section: Introductionmentioning
confidence: 99%
“…The prerequisites for stable positioning of an implant are restoring neutral limb alignment and establishing adequate soft tissue balance [3,4]. Malalignment may be related to pain, stiffness, instability, wear, osteolysis and increased risk of loosening [5][6][7][8]. It has been demonstrated that a varus or valgus malalignment of the mechanical axis of the operated limb > 3°is associated with up to 20 % higher incidence of implant loosening [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of orthopaedic surgeons continue to strive for neutral, postoperative mechanical alignment; however, this objective remains elusive with conventional intramedullary and extramedullary cutting guides demonstrating difficulty in reproducing this target reliably [9,17,18,24].…”
Section: Introductionmentioning
confidence: 99%